Exploration of the Quality of Life in Iranian Morbid Obese People: A Qualitative Study - Negar Yazdani; Farkhondeh Sharif; Nasrin Elahi; Seyed Vahid Hosseini; Abbas Ebadi (Shiraz University of Medical Sciences, 2019)
Background: Morbid obesity (body mass index≥40 kg/m2 or >35 kg/m2 with co-morbidity) is an important factor in reducing the quality of life which is influenced by the characteristics of the individual, his social, cultural, and environmental conditions; also, each disease has unique effects on it. Although most of the studies have been conducted on obesity (25>BMI>40), how to prevent it and improve life quality, there is lack of knowledge about what morbid obese people really experience about their life quality. Thus, this qualitative study aimed to explore the viewpoints of morbid obese people about life quality. Methods: In this conventional content analysis, data were collected using semi-structured interviews with 20 morbid obese patients who were referred to nutrition and obesity clinics of Shiraz and Ahvaz Jundishapur University of Medical Sciences. Purposeful sampling was processed from May 2016 to January 2017. The sampling continued until data saturation. Each interview was recorded by audio recorder and typed in the MAXQDA10 software. Data were analyzed after each interview. The meaning units were encoded and the codes were categorized. This trend continued until the main and sub-categories emerged. Results: Data analysis indicated 1835 codes, 76 sub-subcategories, 26 subcategories and 6 main categories including physical changes, psychological experiences, socio-personal dysfunction, negative body image, financial pressure, and change in the spirituality. Conclusion: Final results indicated that life quality had a special definition in morbid obesity and includes very different dimensions. This study can promote health care providers' knowledge (nurses) for supporting obese people and improving their quality of life by community-based care approaches.